2018
DOI: 10.1016/j.neuroimage.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion time dependence of microstructural parameters in fixed spinal cord

Abstract: Biophysical modelling of diffusion MRI is necessary to provide specific microstructural tissue properties. However, estimating model parameters from data with limited diffusion gradient strength, such as clinical scanners, has proven unreliable due to a shallow optimization landscape. On the other hand, estimation of diffusion kurtosis (DKI) parameters is more robust, and its parameters may be connected to microstructural parameters, given an appropriate biophysical model. However, it was previously shown that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
193
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(208 citation statements)
references
References 84 publications
15
193
0
Order By: Relevance
“…Determining which of these two "branches" yields physically correct parameter estimates has been subject of some debate [38,73,74] and is not yet fully resolved. In Hansen et al [38] affected parameters are reported for both branches.…”
Section: Fast Estimation Of White Matter Biomarkers Using Axisymmeticmentioning
confidence: 99%
See 4 more Smart Citations
“…Determining which of these two "branches" yields physically correct parameter estimates has been subject of some debate [38,73,74] and is not yet fully resolved. In Hansen et al [38] affected parameters are reported for both branches.…”
Section: Fast Estimation Of White Matter Biomarkers Using Axisymmeticmentioning
confidence: 99%
“…The solutions for the two branches are much more obvious than in conventional WMTI, where the sign choice is only known to be stable over diffusion encoding directions for the branch defined by D a ≤ D e,|| [2]. WMTI analysis based on modest data makes it feasible to experimentally investigate the unresolved branch duality-e.g., using data acquisitions employing varying diffusion times as in Jespersen et al [73] which would have been prohibitively time consuming with conventional WMTI. Similarly, the increase in acquisition speed facilitates high resolution data acquisitions for validation purposes or for in vivo applications.…”
Section: Fast Estimation Of White Matter Biomarkers Using Axisymmeticmentioning
confidence: 99%
See 3 more Smart Citations